Glycemic control in intensive care unit: Experience of a tertiary care center - Hadil A Alotair; Shereen Ahmed Aldasoqi; Juren P Baldove; Mohammed Ahmed Abdou (Wolters Kluwer Medknow Publications, 2019)
Background: Hyperglycemia complicates the course of illness of many critically ill patients and contributes to the increased morbidity and mortality in adult intensive care units (ICUs). Objective: The objective of this study is to compare the effectiveness of a modified nurse-implemented insulin infusion protocol (NIIP) against the original protocol used in the adult ICUs, in terms of controlling hyperglycemia while averting significant hypoglycemia. Methodology: Blood glucose (BG) readings that were collected over 3 months in medical and surgical ICUs (SICUs) while on the original insulin infusion protocol were retrospectively reviewed. A modified insulin infusion protocol was prepared by a dedicated adult ICU quality focus group composed of physicians, nurses, clinical pharmacists, and quality representative. The rate of insulin infusion was increased by 10%-20% for the BG ranges above 13.1 mmol/L, allowing early transition from a mild-to-moderate scale. The new protocol was implemented for 2 months, and BG readings were compared to the results of the original insulin infusion protocol. Results: A total of 3490 BG readings in the medical ICU and 3006 in SICU were analyzed. Hyperglycemia was found in 1743 readings (26.83%) while on the original insulin protocol. When the modified insulin infusion protocol was applied, hyperglycemia was significantly less (19.83%, P < 0.0001) and significantly more readings were in the range of 7.8-10 mmol/L (52.57% vs. 46.54%, P= 0.0001). The reduction in hyperglycemia was more significant in SICU patients (19.20% vs. 31.27%, P < 0.0001). Meanwhile, severe hypoglycemia remained within the benchmark. Conclusions: The modified NIIP achieved fewer episodes of hyperglycemia in critically ill patients while avoiding the deleterious effects of hypoglycemia. This affirms the value of periodic monitoring and adjustment of ongoing protocols in ICUs.